First record of Gracilinanus agilis (Burmeister, 1854) (Mammalia: Didelphidae) for Loreto, Peru - Huamaní, Liz (2009)
We report the first record of Gracilinanus agilis (Mammalia: Didelphidae) for the department of Loreto, Peru. This represents the northermost record of the species.